Structural Investigation of the Oligosaccharide Portion Isolated from the Lipooligosaccharide of the Permafrost Psychrophile Psychrobacter arcticus 273-4 - Angela Casillo; Ermenegilda Parrilli; Sannino Filomena; Buko Lindner; Rosa Lanzetta; Michelangelo Parrilli; Maria Luisa Tutino; Maria Michela Corsaro (Marine Drugs, 2015)
Psychrophilic microorganisms have successfully colonized all permanently cold environments from the deep sea to mountain and polar regions. The ability of an organism to survive and grow in cryoenviroments depends on a number of adaptive strategies aimed at maintaining vital cellular functions at subzero temperatures, which include the structural modifications of the membrane. To understand the role of the membrane in the adaptation, it is necessary to characterize the cell-wall components, such as the lipopolysaccharides, that represent the major constituent of the outer membrane. The aim of this study was to investigate the structure of the carbohydrate backbone of the lipooligosaccharide (LOS) isolated from the cold-adapted Psychrobacter arcticus 273-4. The strain, isolated from a 20,000-to-30,000-year-old continuously frozen permafrost in Siberia, was cultivated at 4 °C. The LOS was isolated from dry cells and analyzed by means of chemical methods. In particular, it was degraded either by mild acid hydrolysis or by hydrazinolysis and investigated in detail by 1H and 13C NMR spectroscopy and by ESI FT-ICR mass spectrometry. The oligosaccharide was characterized by the substitution of the heptose residue, usually linked to Kdo in the inner core, with a glucose, and for the unusual presence of N-acetylmuramic acid.